Dans les pas de la nuit. Les rythmes urbains de Beyrouth à la tombée du jour - Marie Bonte; Louis Le Douarin (Revue des Mondes Musulmans et de la Méditerranée)
This paper attempts to extend the field of study in urban rhythms by focussing on the gradual transition from day to night life in Beirut. It considers the urban nightscape as a specific time and space whose boundaries are changing and volatile. The fieldwork led to identification of a transition moment, a passing from day to night. This moment of passing seems to condense and focus the city’s rhythms, leading to an urban theatre for which the streets are the stage. At city scale, Beirut looks like an archipelago. This new geography reveals a divided city where representations and rhythms interact and impact on trajectories and spatial practices.